TPR: The Implementation of Speech Acts (Directives) in Classrooms - Barans Irawan Palangan (English Language and Education Spectrum, 2022)
One of the key factors to win global competition is mastering international language, English. In Indonesia, this language is considered as a foreign language and whenever a language has status as foreign language, it is certainly that teaching this language is more challenging. Teaching foreign language particularly English must involve two related field of study, language teaching (pedagogy) and applied linguistics. These two fields of study have made collaboration in order to solve the problem coming English language teaching. This article will describe about the implementation of one of speech acts, (directives), in children classrooms to teach tenses and aspects in the form Total Physical Response (TPR), method in children based on one of SLA grand theories, behaviorism.